Roy Scranton's war porn: an American postcolonial narrative of the Iraq War - Alosman, M Ikbal M; Ruzy Suliza Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper examines Roy Scranton’s debut novel, War Porn (2016), and aims to uncover the novel’s approach to the 2003 American war on Iraq and its impact on the lives of Iraqis. It problematizes the representation of the Iraqi people in the context of the American invasion and presence in Iraq after the 2003 war. Postcolonial literature challenges the cultural hegemony imposed by colonial powers by demonstrating the richness, diversity, and vitality of their culture. It illustrates the negative influence of colonialism on the colonized and emphasizes its impact on the people and the land of the colonized. The argument is made through three constructs: “postcolonial voices,” which addresses the diverse Iraqi perspectives on the war as represented in the novel, “colonial repercussions and implications,” which elaborates on the disastrous influence of colonization on the lives of Iraqis, and “postcolonial representations,” which explores the depth and richness of Iraqi culture as exemplified in the novel. The study argues that Scranton’s is a postcolonial novel par excellence, albeit ironically written by an American veteran who participated in the very colonial endeavour he questions in his war narrative. It is one of the few acclaimed American war novels to devote a significant narrative space to recounting the 2003 war from the perspective of major Iraqi characters, reflecting the richness of Iraqi culture and the negative impact of colonialism on Iraq and Iraqis.